URDU-CRITICISM OF AIYMA NAQAAD (THE CRITICS) ON THE RAVI IN THE TERM OF PERSONAL STATUS RESEARCH AND ANALYTICAL STUDY OF DIFFERENCES OF MUHADDITHIN - Muhammad Rizwan (دی اسکالر, 2019)
There is no work of the world in which man is involved and there is no disagreement. So disagreement is a natural process between human beings. People have different views and opinions in their ways of life according to their knowledge and wisdom. Religion and culture also affect people’s thinking.  As ordinary human beings, there has been a difference of opinion between Mohaddethin in regard of the health and weaknesses of Rawayan-e-Hadeeth. But it is extremely important to understand the disagreement of critics (Aima-Niqad) and evaluate their causes compared to differences in all walks of life.  Because it is related to  Hadith-e- Rasool which is the interpretation of Quran and the  second primary source of  Islam. So that the doubts and suspicions created in the mind of people can be removed.  Basically, the disagreement in trustworthiness and duplication of Ruwath is either according to the personal status of critics or principles of Jarah-o-Tadeel and in the term of their application. According to the personal status of critics there are many causes of disagreements of Mohaddethin. Aima-Niqad are different about the vastness of knowledge from each other. Due to this difference of knowledge, some Mohaddethin are familiar with the living condition of all narrators but some Mohaddethin are not aware of the general conditions or specific weakness of some narrators. Due to this difference in knowledge, Mohaddethin disagree in ordering the narrators. Some times this difference of knowledge is in the Hadith. Some of the critics are familiar with all the Hadith of the narrator. But some Aima-Niqad are ignorant of the all Hadith of narrator or Hadith of any particular shiekh or the city which are not trustworthy. Due to this reason there is a disagreement in ordering the narrators. Due to different temperaments, some become violent, aggressive and some become moderate in ordering the Hadith. So, different natures of Mohaddethin are also effective on the narrators. Some, critics due to the achievement of worldly goals, impose unjust ruling, due to their difference in the opinion of Mohaddethin about the narrators. Mistakes are the weakness of human beings,   some Mohaddethin also made a mistake in the matter of ruling on Rawayat, due to reasons of human weakness there is a disagreement with the other Mohaddethin.